2016
DOI: 10.1007/s10517-016-3242-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin in the Regulation of Differentiation of T Cells Producing Interleukin-17 (Th17)

Abstract: We studied the ability of melatonin in physiological and pharmacological concentrations to induce and/or regulate differentiation of T cells producing IL-17 (Th17). This hormone produced the opposite effect on CD4+T cells, which depended on their activation status. Melatonin induced the synthesis of IL-17A by intact T cells, but had little effect on activated cells. Melatonin in high (pharmacological) concentration decreased the intracellular expression of this cytokine under conditions of polyclonal activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Sleep disorders: These needed to be addressed by treating Lyme and associated coinfections, as well as ruling out other causes of sleep related problems (such as OSA, RLS, BPH, depression, anxiety, long acting stimulant and/or caffeine use). Treatment of insomnia using various medications (i.e., trazadone, tiagabine, mirtazapine, cyclobenzaprine, and pregabalin) and herbal therapies which support sleep and the circadian rhythm (i.e., valerian root and melatonin, which also lowers IL-17) were often needed [189]. Chart review indicated that balancing hormones (phosphatidylserine can be used to lower high adrenal function at night) [190] while stimulating GABA receptors (using GABA L-theanine) also were occasionally helpful in getting the patient to sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders: These needed to be addressed by treating Lyme and associated coinfections, as well as ruling out other causes of sleep related problems (such as OSA, RLS, BPH, depression, anxiety, long acting stimulant and/or caffeine use). Treatment of insomnia using various medications (i.e., trazadone, tiagabine, mirtazapine, cyclobenzaprine, and pregabalin) and herbal therapies which support sleep and the circadian rhythm (i.e., valerian root and melatonin, which also lowers IL-17) were often needed [189]. Chart review indicated that balancing hormones (phosphatidylserine can be used to lower high adrenal function at night) [190] while stimulating GABA receptors (using GABA L-theanine) also were occasionally helpful in getting the patient to sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The release of proinflammatory cytokines, such as IL‐1β (in earlier studies, IL‐1), IL‐2, IL‐6, IL‐12, TNFα, and IFNγ in response to melatonin has been repeatedly observed in monocytes, monocyte‐derived cells and T‐helper cells type 1, of IL‐17 in non‐preactivated Th17 cells, and of IL‐1β, TNFα and IFNγ in splenocytes, too . Although most studies clearly point into this direction, deviating findings have also been published.…”
Section: Proinflammatory Actions As Revealed By Studies On Immune Cellsmentioning
confidence: 96%
“…Notably, these findings can be seen in the context of pro-oxidant and cytotoxic effects exerted by melatonin in monocytes, as observed above an activation threshold as low as 50 pM [55]. Moreover, melatonin was found to increase another proinflammatory cytokine, IL-17A, in Th17 cells [56], an effect that spreads proinflammatory responses by inducing the release of other mediators, such as IL-1β, IL-6, TNFα, the neutrophil-attracting Il-8, and by upregulating cyclooxygenase-2 (COX-2) and iNOS (inducible NO synthase) [57,58,59,60,61,62,63,64,65]. This host of secondary effects by IL-17A has been shown to be involved in autoimmune diseases and in neuroinflammation and is, therefore, of relevance to age-related health problems and to adverse effects of melatonin, especially in autoimmunity.…”
Section: Melatonin and The Proinflammatory Networkmentioning
confidence: 99%